2008
DOI: 10.1007/s11095-007-9498-7
|View full text |Cite
|
Sign up to set email alerts
|

The USP Performance Verification Test, Part I: USP Lot P Prednisone Tablets—Quality Attributes and Experimental Variables Contributing to Dissolution Variance

Abstract: Statistical analysis demonstrated that dissolution test assemblies were the largest factor contributing to dissolution variability. Inherent tablet variability was low, and USP Lot P Prednisone Tablets did not contribute importantly to dissolution variability. Contributions from analyst and analytical procedure also were estimated to be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…This is consistent with data from experiments under normal (nonperturbed) conditions that have shown relatively low variability using USP Prednisone RS Tablets (6). These findings may also help explain previous data that show low intralaboratory variability but high interlaboratory variability of prednisone dissolution results (5).…”
Section: Variabilitysupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with data from experiments under normal (nonperturbed) conditions that have shown relatively low variability using USP Prednisone RS Tablets (6). These findings may also help explain previous data that show low intralaboratory variability but high interlaboratory variability of prednisone dissolution results (5).…”
Section: Variabilitysupporting
confidence: 90%
“…This has led USP to conduct a comprehensive set of studies to examine potential assembly deviations that contribute to this variability. This study is one of a series of reports of these investigations (3)(4)(5)(6). Based on these studies, USP may change statements in <711> and allied documents to assist manufacturers in improving the USP Performance test when the dissolution procedure is chosen.…”
mentioning
confidence: 99%
“…Tanaka et al have shown that minimizing the irregularities in the inner surface of glass dissolution vessels leads to lower variability in dissolution tests with USP Lot O Prednisone Reference Standard Tablets (5). Recent dissolution variance studies conducted by USP suggest that the dissolution vessel and apparatus source can be a major cause of variability in dissolution results (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…However, apparatus performance may contribute to interlaboratory variability as demonstrated from the results generated in laboratories that participated in global collaborative trials (3).…”
Section: Enhanced Mechanical Qualification-iq and Oq Checkpoints And mentioning
confidence: 99%